2016
DOI: 10.2217/pmt.16.9
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Neuropsychiatric Correlates of Lumbar Spinal Surgery in Older Adults: Results of a Pilot Study

Abstract: Aim:To improve selection of older lumbar surgical candidates, we surveyed correlates of functioning and satisfaction with surgery. Materials & methods: Prospective sample at lumbar spine surgery clinic. Patients (n = 48) were evaluated before surgery and after 3 months. Dependent variables were functioning and surgical satisfaction. Results: Baseline variables associated with disability at 3 months included cognitive status and widespread pain. There was clinically significant improvement with moderate effects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…The increasing number of affected patients and the growing socioeconomic consequences of DLSS underscore the need for an accurate diagnosis. Clinical judgement is generally based on symptom severity, functional deficits, physical examination and radiographic imaging [6]. However, psychological and sociodemographic factors as well as the course of disease, seem to influence the clinical presentation of DLSS (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The increasing number of affected patients and the growing socioeconomic consequences of DLSS underscore the need for an accurate diagnosis. Clinical judgement is generally based on symptom severity, functional deficits, physical examination and radiographic imaging [6]. However, psychological and sociodemographic factors as well as the course of disease, seem to influence the clinical presentation of DLSS (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…There is no “gold standard” for the diagnosis of DLSS [5]. Clinical judgement is generally based on symptom severity, functional deficits, physical examination and radiographic imaging [6]. The most promising imaging test is magnetic resonance imaging (MRI) [5].…”
Section: Introductionmentioning
confidence: 99%
“…13 In elderly patients undergoing lumbar spinal surgery, postoperative improvement in sleep quality has been demonstrated to correlate with improvements in disability. 14 A study by Yavuz and Uysal 15 demonstrated that, after single-level lumbar microdiscectomy, patient-reported sleep quality improved by 64% compared with patients who underwent extended conservative therapy who reported sleep improvement by 38%, in a similar pattern as pain improvement between groups. A retrospective review by Hu et al 16 demonstrated that 82% of patients with thoracolumbar kyphosis secondary to ankylosing spondylitis reported poor sleep at baseline.…”
Section: Sleep Quality and Spine Surgerymentioning
confidence: 98%
“…In a systematic review focusing on sleep disruption and chronic low back pain, it was observed that improvements in self-reported sleep duration and quality were significantly associated with improvements in lower back pain 13. In elderly patients undergoing lumbar spinal surgery, postoperative improvement in sleep quality has been demonstrated to correlate with improvements in disability 14. A study by Yavuz and Uysal15 demonstrated that, after single-level lumbar microdiscectomy, patient-reported sleep quality improved by 64% compared with patients who underwent extended conservative therapy who reported sleep improvement by 38%, in a similar pattern as pain improvement between groups.…”
Section: Sleep Quality and Spine Surgerymentioning
confidence: 99%